Synthesis mechanism from graphene quantum dots to carbon nanotubes by ion-sputtering assisted chemical vapor deposition - Jun Mok Ha; Seoung Ho Lee; Daehyeon Park; Young Jun Yoon; In Mok Yang; Junhyeok Seo; Yong Seok Hwang; Chan Young Lee; Jae Kwon Suk; Jun Kue Park; Sunmog Yeo (Discover Nano, 2024)
Abstract We present the first work of the synthesis mechanism from graphene quantum dots (GQDs) to carbon nanotubes (CNTs) by an ion-sputtering assisted chemical vapor deposition. During the annealing process, a Pt thin film deposited by the ion-sputtering was dewetted and agglomerated to form many nanometer-sized particles, leading to Pt nanoparticles (PtNPs) that can act as catalysts for creating carbon allotropes. The shape of the allotropes can be effectively tailored from GQDs to CNTs by controlling three key parameters such as the dose of catalytic ions (D), amounts of carbon source (S), and thermal energy (T). In our work, it was clearly proved that the growth control from GQDs to CNTs has a comparably proportional relationship with D and S, but has a reverse proportional relationship with T. Furthermore, high-purity GQDs without any other by-products and the CNTs with the cap of PtNPs were generated. Their shapes were appropriately controlled, respectively, based on the established synthesis mechanism. Graphical abstract